Islamic Education Policy Reform: Political Dynamics and Curriculum Reorientation in the Merdeka Belajar Era - Alif Fatoni; Bahrul Ulum; Jamaluddin Akbar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to conduct a multidimensional analysis of Islamic education policy reform in Indonesia (2021-2026) through three main pillars: political-regulatory contestation, curriculum reorientation, and digital governance. Utilizing a Systematic Literature Review (SLR) with the PRISMA protocol, the study synthesizes 60 key policy documents and reputable journal articles. Findings reveal that while madrasas have achieved formal legal equality,